EVALUASI PROGRAM KAMPUNG SEDEKAH PADA YAYASAN SEDEKAH NGIDER DALAM MEMBERDAYAKAN MASYARAKAT DI KELURAHAN KELAPA DUA WETAN JAKARTA TIMUR - Arini Sisi Nabillah; Hera Diana Tansia; Nadia Anggraini; Tina Sagitasari (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2021)
The purpose of this study is to describe the evaluation of empowerment programs using the CIPP evaluation model (Context, Input, Process, Product). This research approach uses kualitatif methods. The research subjects consisted of the Sedekah Ngider Foundation, village administrators and members of the sedekah village. Data collection techique used is data reduction, data presentation and conclusions. In conclusion, the result of the context evaluation on the village alms program have been achieved and the needs of the community have been met. The input evaluation, which includes implementers, budget allocatons, targets, facilities and infrastructure supporting the program has been achieved due to good cooperation from the Sedekah Ngider Foundation and the Sedekah village administrators. Process evaluation includes planning and socialization, implementation monitoring and evaluation of the program in accordance with the process. Product evaluation consisting of program results, according to research that has been carried out vy the village sedekah program, has been achieved in empowering the community in gaining skills and knowledge.